The Implementation of the RAD model in the Development of Tender Selection Programs Using the AHP Method - Rudianto Rudianto (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2020)
The activity of selecting bidders is one of the most important activities carried out by companies to order goods or services for bidders, but at meetings of the company leadership it is difficult to select bidders to make business partners because there are only a few things that are not in accordance with who agree to end the shipment of goods, prices do not match and end the company that receives losses. That is caused by the lack of competence of selected tender partners. From the problems mentioned above, the tender selection process that has been conducted so far is still lacking and inaccurate. The purpose of this study is to create an application program using the Rapid Application Development Model (RAD Model) that can assist leaders in selecting business partners through a tender process by giving weights according to the criteria specified requirements. It is expected that the tender selection process is objective and accurate. Assessment method Decision making (SPK) Analytichal Hierarchy Process (AHP) method is one method in the process of resolution by completing each case by completing it first by using weighting criteria. In the end the selection application program can help lead in making objective, fast and accurate decisions.